Differential expression of midgut proteins in Trypanosoma brucei gambiense-stimulated vs. non-stimulated Glossina palpalis gambiensis flies - Geiger, Anne; Hamidou Soumana, Illiassou; Tchicaya, Bernadette; Rofidal, Valérie; Decourcelle, Mathilde; Santoni, Véronique; Hem, Sonia (Frontiers in Microbiology, 2015)
The unicellular pathogenic protozoan Trypanosoma brucei gambiense is responsible for the chronic form of sleeping sickness. This vector-borne disease is transmitted to humans by the tsetse fly of the group Glossina palpalis, including the subspecies G. p. gambiensis, in which the parasite completes its developmental cycle. Sleeping sickness control strategies can therefore target either the human host or the fly vector. Indeed, suppression of one step in the parasite developmental cycle could abolish parasite transmission to humans, with consequences on the spreading of the disease. In order to develop this type of approach, we have identified, at the proteome level, events resulting from the tripartite interaction between the tsetse fly G. p. gambiensis, its microbiome, and the trypanosome. Proteomes were analyzed from four biological replicates of midguts from flies sampled three days post-feeding on either a trypanosome-infected (stimulated flies) or a non-infected (non-stimulated flies) bloodmeal. Over 500 proteins were identified in the midguts of flies from both feeding groups, thirteen of which were shown to be differentially expressed in trypanosome-stimulated versus non-stimulated flies. Functional annotation revealed that several of these proteins have important functions that could be involved in modulating the fly infection process by trypanosomes (and thus fly vector competence), including anti-oxidant and anti-apoptotic, cellular detoxifying, trypanosome agglutination, and immune stimulating or depressive effects. The results show a strong potential for diminishing or even disrupting fly vector competence, and their application holds great promise for improving the control of sleeping sickness.